2010
DOI: 10.1111/j.1600-0765.2008.01199.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral malodorous compound triggers mitochondrial-dependent apoptosis and causes genomic DNA damage in human gingival epithelial cells

Abstract: Hydrogen sulfide induces apoptosis in human gingival epithelial cells by activating the mitochondrial pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
64
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 39 publications
2
64
0
1
Order By: Relevance
“…D. oralis encodes several sulfatases that could liberate inorganic sulfate from GAGs, potentially playing an active role in matrix destruction (93). In addition, the hydrogen sulfide produced by D. oralis during sulfate respiration can lead to apoptosis in keratinocytes (82,94) and further elicits a proinflammatory response in oral cells (95,96). These features illustrate the capacity of D. oralis to create a dysbiotic oral environment and actively contribute to the pathogenesis of periodontal disease in a novel and compounded way not described for other oral pathogens so far.…”
mentioning
confidence: 99%
“…D. oralis encodes several sulfatases that could liberate inorganic sulfate from GAGs, potentially playing an active role in matrix destruction (93). In addition, the hydrogen sulfide produced by D. oralis during sulfate respiration can lead to apoptosis in keratinocytes (82,94) and further elicits a proinflammatory response in oral cells (95,96). These features illustrate the capacity of D. oralis to create a dysbiotic oral environment and actively contribute to the pathogenesis of periodontal disease in a novel and compounded way not described for other oral pathogens so far.…”
mentioning
confidence: 99%
“…67 A number of studies showed the positive relation between progression of periodontal disease and VSC amount. 35,36 Morita and Wang 68 found a significant relation between the severity of periodontal disease and VSC amount in breath. They discovered that VSC value was measured lower within people who are provided with periodontal treatment than the ones who are not treated.…”
Section: Discussionmentioning
confidence: 97%
“…The initial apical migration of junctional epithelium in lipopolysaccharideinduced experimental periodontitis appeared to occur simultaneously with the apoptosis of periodontal ligament fibroblasts. [25][26][27] It was therefore suggested that the apoptosis-related detachment of connective tissue may cause the migration of junctional epithelium. Callenic and others found there were two main mechanisms in the apoptotic process involve activation of an intrinsic pathway, in which the mitochondrion plays a central role, and activation of an extrinsic pathway, involving a receptor-ligand-mediated mechanism.…”
Section: Discussionmentioning
confidence: 99%